Perkembangan anak pada masa usia Sekolah - Darul Muadhdham, Imadud; Tri Wisudaningsih, Endah (Jurnal Pendidikan Agama Islam, 2025)
The school years are a crucial period in a child's life because they experience rapid physical, cognitive, emotional, and social development. The purpose of this article is to examine aspects of school-age children's development, the influencing factors, and their implications for the educational process. The study method was a literature review, reviewing various developmental and educational psychology literature. The results indicate that child development during the school years includes improvements in logical thinking skills, social skills, emotional independence, and readiness to face academic demands. Teachers and parents play a crucial role in providing appropriate stimulation through a conducive learning environment. In conclusion, understanding child development during the school years is crucial for educators and parents in developing effective learning strategies. The research method used was a qualitative literature study approach. Data analysis was conducted through reduction, presentation, and conclusions using an inductive approach. The results indicate that child development during the school years is strongly influenced by interactions between the family, school, and community environments. Internal factors such as learning motivation, personality, and emotional readiness also play a significant role